2014
DOI: 10.1038/jcbfm.2014.82
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Molecular Imaging of Serotonin Transporters in Major Depression

Abstract: The success of serotonin-selective reuptake inhibitors has lent support to the monoamine theory of major depressive disorder (MDD). This issue has been addressed in a number of molecular imaging studies by positron emission tomography or single-photon emission computed tomography of serotonin reuptake sites (5-HTT) in the brain of patients with MDD, with strikingly disparate conclusions. Our meta-analysis of the 18 such studies, totaling 364 MDD patients free from significant comorbidities or medication and 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(105 citation statements)
references
References 85 publications
(90 reference statements)
9
95
1
Order By: Relevance
“…Earlier research in this population has shown that TNF antagonism was associated with an antidepressant effect that was independent of disease improvement (Gelfand et al, 2008;Krishnan et al, 2007;Langley et al, 2010;Tyring et al, 2006). Consistent with previous studies, TNF-α explained only around 3% of and brain stem 5-HTT availability explained only around 7% variance in depression severity (Gryglewski et al, 2014;Valkanova et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Earlier research in this population has shown that TNF antagonism was associated with an antidepressant effect that was independent of disease improvement (Gelfand et al, 2008;Krishnan et al, 2007;Langley et al, 2010;Tyring et al, 2006). Consistent with previous studies, TNF-α explained only around 3% of and brain stem 5-HTT availability explained only around 7% variance in depression severity (Gryglewski et al, 2014;Valkanova et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Our study is the first to show in vivo effects of vortioxetine on platelet 5-HT concentrations in depressed patients, as other studies have only been conducted on healthy and younger subjects (Areberg et al 2012;Stenkrona et al 2013). A meta-analysis of molecular imaging data revealed reductions of around 10% availability in 5-HT reuptake sites in different brain regions in drug-naïve depressed patients compared to healthy subjects (Uebelhack et al 2006), which were further reduced with increased age (Gryglewski et al 2014;Rominger et al 2015). SSRIs have been found to modulate 5-HT concentration in a similar manner in platelets and neurons (Yubero-Lahoz et al 2013), and theoretically, the higher the central SERT occupancy, the lower the platelet 5-HT concentration.…”
mentioning
confidence: 52%
“…The SERT is responsible for 5-HT reuptake from the synaptic cleft and thus determines the magnitude and duration of the 5-HT synaptic signal. A reduction of SERT sites in the brain (particularly in midbrain and amygdala) of depressed patients has been demonstrated both by functional imaging (Gryglewski et al 2014;Yeh et al 2014) and post-mortem brain studies (Mann et al 2000). As the binding to the SERT and the 5-HT uptake capacity remain low after recovery, low SERT activity has been suggested as a trait marker for mood disorders (Lesch 2001).…”
Section: Serotonin Transportermentioning
confidence: 99%